2000
DOI: 10.1002/1097-0088(200009)20:11<1285::aid-joc536>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and climatic signals across the Indian Ocean Basin in the global context: part I, interannual composite patterns

Abstract: This study focuses on the interplay between mean sea level pressure (MSLP), sea surface temperature (SST), and wind and cloudiness anomalies over the Indian Ocean in seasonal composite sequences prior to, during, and after strong, near-global El Niñ o and La Niñ a episodes. It then examines MSLP and SST anomalies in the 2 -2.5-year quasi-biennial (QB) and 2.5-7-year low-frequency (LF) bands that carry the bulk of the raw ENSO signal. Finally, these fields were examined in conjunction with patterns of correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
107
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 63 publications
16
107
1
Order By: Relevance
“…Reason et al [2000] described a similar wind curl pattern due to ENSO, but with anomalies extending further east into the Indonesian passages. Furthermore, anomalous winds around Indonesia due to both the IOD and ENSO alter the normal Indo-Pacific sea level gradient, which is the driving force of the Indonesian Throughflow (ITF): during El Niño (La Niña) events, a lower (higher) ITF transport is expected, and vice versa for the IOD phases [Meyers, 1996].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Reason et al [2000] described a similar wind curl pattern due to ENSO, but with anomalies extending further east into the Indonesian passages. Furthermore, anomalous winds around Indonesia due to both the IOD and ENSO alter the normal Indo-Pacific sea level gradient, which is the driving force of the Indonesian Throughflow (ITF): during El Niño (La Niña) events, a lower (higher) ITF transport is expected, and vice versa for the IOD phases [Meyers, 1996].…”
Section: Introductionmentioning
confidence: 85%
“…highly energetic eddies) in 1995and of low EKE in 1997and 2000-2001, with an EKE amplitude of 600 -800 cm 2 /s 2 (Figure 5a). Interestingly, this interannual variation is not present in the EKE in northern regions of the MZC.…”
Section: Eke Interannual Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been shown that other years display similar patterns to ENSO in this large region [Meehl, 1987;Lau and Wu, 2001]. In fact, the strength of TBO and ENSO signals is closer in magnitude over the Indian Ocean than the equatorial Pacific (Reason et al, 2000). Therefore the TBO must include most ENSO (El Nifio and La Nifia) years and some other years as well.…”
Section: Introductionmentioning
confidence: 99%